KIDUNG RUMEKSA ING WENGI (Studi Tentang Naskah Klasik Bemuansa Islam) - Achmad Sidiq (Balai Penelitian dan Pengembangan Agama Semarang, 2008)
Kidung Rumeksa ing Wengi (precaution at night) is a songcomposed by Sunan Kalijaga. He is one of Walisongo, Islamicmissioner in Java. He is well known because of his skills and wisdomin propagating Islam with its source in Al 'Quran and Al-Hadist bytransforming it into Javanese community through various missionarymedium. One of them is his teaching in Javanese prayers (charms).Prayers in Javanese are often in form of songs or charmssince it is believed has magical power for those who practice it. Kidung Rumeksa ing Wengi, this charm is also known as